Karateristik Medan Kecepatan Aliran Setelah Melewati Internal Flow Double Skewed Wall Cyclone (IFC2SW) - Widayana, Gede (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2013)
Efforts to improve the performance of the motor fuel is to add a cyclone before the carburetor that functions to increase the homogeneity of the mixture of air and fuel. In this study, conducted aerodynamic testing in line with Internal Flow Double Cyclone skewed Wall (IFC2SW) to be able to know how big the flow characteristics of the velocity field that arises after passing IFC2SW. The main parameters that will be used as an indicator is that the velocity profile obtained from the measurement of total pressure and static pressure in the duct cross section. Results showed that the characteristics of the velocity field after passing IFC2SW evenly along both the center channel and the channel wall.Keywords : Cyclone, Internal Flow Cyclone Double Skewed Wall